2013
DOI: 10.1016/j.yjmcc.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic analysis of two different models of delayed preconditioning

Abstract: Recently we described an ischemic preconditioning induced by repetitive coronary stenosis, which is induced by 6 episodes of non-lethal ischemia over 3 days, and which also resembles the hibernating myocardium phenotype. When compared with traditional second window of ischemic preconditioning using DNA microarrays, many genes which differed in the repetitive coronary stenosis appeared targeted to metabolism. Accordingly, the goal of this study was to provide a more in depth analysis of changes in metabolism in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…46 Since the brain evolved to support robust metabolic responses in active neurons and circuits while minimizing resting global energy expenditure, 47 a PBM-induced increase in brain PCr levels could help supply the on-demand energy necessary for rapid circuit activation, thereby improving brain func-tion, as reported previously. 10,[21][22][23][24][25][26][27][28] PCr elevations in the heart and brain have been associated with preconditioning stimuli, [48][49][50] and preconditioning effects of PBM have been described in multiple tissues. 1,13,46 Accordingly, it is possible that PBM-associated elevations in the PCr/b-NTP ratio and PCr we detected at the scan session 2 baseline could reflect a cortical preconditioning effect of TLT.…”
Section: Discussionmentioning
confidence: 99%
“…46 Since the brain evolved to support robust metabolic responses in active neurons and circuits while minimizing resting global energy expenditure, 47 a PBM-induced increase in brain PCr levels could help supply the on-demand energy necessary for rapid circuit activation, thereby improving brain func-tion, as reported previously. 10,[21][22][23][24][25][26][27][28] PCr elevations in the heart and brain have been associated with preconditioning stimuli, [48][49][50] and preconditioning effects of PBM have been described in multiple tissues. 1,13,46 Accordingly, it is possible that PBM-associated elevations in the PCr/b-NTP ratio and PCr we detected at the scan session 2 baseline could reflect a cortical preconditioning effect of TLT.…”
Section: Discussionmentioning
confidence: 99%
“…67 The results of a recent metabolomic analysis of ischemic VD pig myocardium were supportive of these data, showing a reduction in TCA cycle metabolites α-ketoglutarate, succinate, fumarate and malate. 68 Moreover, the intermediates of lipid metabolism, carnitine, acetylcarnitine and palmitoylcarnitine, were also reduced in VD myocardium. 68 Thus, mitochondrial oxidative phosphorylation is consistently suppressed in VD myocardium of humans and animals.…”
Section: Molecular Mechanisms Of Vd Myocardiummentioning
confidence: 96%
“…68 Moreover, the intermediates of lipid metabolism, carnitine, acetylcarnitine and palmitoylcarnitine, were also reduced in VD myocardium. 68 Thus, mitochondrial oxidative phosphorylation is consistently suppressed in VD myocardium of humans and animals.…”
Section: Molecular Mechanisms Of Vd Myocardiummentioning
confidence: 96%
See 1 more Smart Citation
“…As such, the frequency and magnitude of the metabolite changes was higher in those animals subjected to repetitive coronary stenosis (6 episodes of non-lethal ischemia over 3 days prior to the ischemic insult) as compared to those that underwent second window of ischemic preconditioning (two episodes of total left anterior descending coronary artery occlusion for 10 min and 10 min of reperfusion, followed by 24 h of reperfusion). Most interestingly, most of the altered cardiac metabolites found in repetitive coronary stenosis were linked to mechanisms known to improve energy metabolism [72]. Regarding lipidomics, we have recently reported that the attenuation of HDL-related cardioprotection in the setting of hypercholesterolemia might be associated with lipidomic changes in the HDL micelles, losing phosphatidylcholine-lipid species (involved in HDL functionality) and gaining cholesteryl esters (involved in HDL maturation and loss of function) [58].…”
Section: Implementation Of Post-genomic Technologies In Preclinicamentioning
confidence: 99%